2009
DOI: 10.1016/j.pbb.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect 5-HT receptor agonists produce gender-specific effects on locomotor and vertical activities in C57 BL/6J mice

Abstract: It is well established that the dopamine (DA) and serotonin (5-HT) systems have extensive and complex interactions. However, the effects of specific 5-HT receptor agonists on traditionally DA-related behaviors remain unclear. Our goal in these studies was to characterize the effects of 5-HT receptor agonists on measures of locomotor activity and vertical rearing. The SSRIs fluoxetine and citalopram produced significant decreases in locomotor activity and vertical rearing at the highest doses used with females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 48 publications
6
17
0
Order By: Relevance
“…Similar to our findings, other groups have reported that DOI increases locomotor activity in mice (Darmani et al, 1996; Brookshire and Jones, 2009). There is also evidence that low doses of DOM can increase locomotor activity and reduce rearing behavior in ddN mice (Yamamoto and Ueki, 1975).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar to our findings, other groups have reported that DOI increases locomotor activity in mice (Darmani et al, 1996; Brookshire and Jones, 2009). There is also evidence that low doses of DOM can increase locomotor activity and reduce rearing behavior in ddN mice (Yamamoto and Ueki, 1975).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, these discrepant findings are most likely a consequence of differences in study design, and the duration of the open field studies with DOI and TCB-2 may not have been long enough to detect hyperactivity induced by those agents. In contrast to our BPM studies, which were conducted during the dark phase of the light-dark cycle, Fox et al (2010) tested DOI and TCB-2 during the light phase; it is unlikely, however, that this contributed to the discrepant findings because DOI has also been shown to induce hyperactivity during the light-phase (Brookshire and Jones, 2009). …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Phenylalkylamines, including DOI, mescaline, and TCB-2, inhibit investigatory behavior and alter locomotor activity in a dose-dependent manner, increasing activity at low to moderate doses and reducing activity at high doses (Halberstadt et al, 2009, 2013). Other groups have reported similar findings with DOM and DOI in mice (Yamamoto and Ueki, 1975; Darmani, 1996; Brookshire and Jones, 2009; Carlsson et al, 2011). The increase in locomotor activity induced by 1 mg/kg DOI, 25 mg/kg mescaline, or 3 mg/kg TCB-2 is blocked by low doses of M100907 and is absent in 5-HT 2A knockout mice.…”
Section: Involvement Of the 5-ht2a Receptor In Hallucinogen Effectssupporting
confidence: 79%
“…In addition to decreased locomotion and stereotypy, we demonstration a cocaine induced increase in vertical activity in cocaine self administering animals. Serotonin levels are inversely related to vertical activity (Brookshire and Jones, 2009); thus, it is possible that the serotonin system may also be affected by cocaine self-administration. Studies of whole brain functional activity after this self-administration paradigm have observed reduced dorsal raphe activity (Calipari et al, 2013c).…”
Section: Discussionmentioning
confidence: 99%